Kepribadian Tokoh Utama dalam Novel "Nyanyian Batanghari" Karya Harry B. Kori’un - Naratungga Indit Prahasita (Gramatika: Jurnal Ilmiah Kebahasaan dan Kesastraan, 2014)
This research aimed at revealing the personalities of the main character in the novel “Nynyian Batanghari” by Harry. B. Kori’un (HBK). Approach to address this problem was the literary psychological approach that emphasized on the theory of Sigmund Freud’s psychoanalysis. The research was focused on the characteristics of the main characters with characterization method, while the researcher used psychoanalysis to analyze the characteristics of the main character. Freud divided the structure of human personality into three components; id, ego, and superego. The technique of collecting data was conducted by reading and taking notes. The characteristics found in the novel were vindictive, brave, stubborn,reliable, desperate, helpful, and regretful. The personality of the main character in Kori’un’s Nyanyian Batanghari was dominated by id-influencing-characteristics. The dominance of id in the main character’spersonality caused her personality to be patterned pleasure principle, so that the individual tends to be have recklessly and aims only at achieving pleasure. That is why the main character’s personality tends to be idealistic and emotional.